2016
DOI: 10.3823/2252
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the quality of life of an elderly group of the family health strategy

Abstract: Background: To analyze the quality of life of a group of elderly people enrolled in the Family Health Strategy of the Igapó neighborhood, in the city of Natal, Rio Grande do Norte, Brazil.Methods: This is a longitudinal study with a quantitative approach.The process of data collection occurred in two different moments. The instruments used to collect data were: "Questionnaire on sociodemographic data" and the "Brazilian Version of the Short Form-36 Quality of Life Questionnaire (SF-36)."Results: It was verifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 14 publications
0
3
0
2
Order By: Relevance
“…In their research, they found the major sources of income among the elderly were money given by their children, followed by the pay from work. Past studies indicated that the "happy elderly" have a higher level of income [17,30] than those "unhappy" ones do since higher income and savings reduces psychological pressure to the future concerns [31]. However, the studies on lower-income demonstrated that inadequate income is a significant problem for elders after retirement, and it would cause low self-esteem [17], depression [31], and difficulties in social participation [30].…”
Section: Low Incomementioning
confidence: 99%
“…In their research, they found the major sources of income among the elderly were money given by their children, followed by the pay from work. Past studies indicated that the "happy elderly" have a higher level of income [17,30] than those "unhappy" ones do since higher income and savings reduces psychological pressure to the future concerns [31]. However, the studies on lower-income demonstrated that inadequate income is a significant problem for elders after retirement, and it would cause low self-esteem [17], depression [31], and difficulties in social participation [30].…”
Section: Low Incomementioning
confidence: 99%
“…A saúde do ser humano, particularmente aquele que sofre de condições de cronicidade, está na dependência do modo de viver, dos hábitos e costumes, da consciência de suas possibilidades e limites ao buscar atendimento ou satisfação de suas necessidades. Estas condições que levam ao estado de necessidades podem ser mais bem conhecidas e satisfeitas com o apoio dos profissionais de saúde através do cuidado especializado (COSTA et al, 2016).…”
Section: Introductionunclassified
“…A longevidade é uma conquista da população mundial, porém, para que essa se torne valiosa, é necessário que os anos a mais sejam acompanhados da preservação da saúde e da qualidade de vida (ORGANIZAÇÃO..., 2015;COSTA et al, 2017). Os indivíduos se tornaram mais longevos, porém esses anos a mais de vida vieram acrescidos de problemas de saúde relacionados com doenças crônicas degenerativas não transmissíveis (DCNT) (BORGES; CAMPOS; SILVA, 2015;BERGERON-BOUCHER;BOURBEAU;LÉGARÉ, 2016).…”
Section: Introductionunclassified